Woman, Self-Giving and Receiving: New Feminism, Theology of the Body, and Society - Aneta Gawkowska (Polonia Sacra)
This paper was originally presented at the “Theology of the Body” International Symposium organized at the Athenaeum Pontificium Regina Apostolorum in Rome, Italy, which was held November 9–11, 2011.